TELEPROM Psoriasis: Enhancing patient-centered care and health-related quality of life (HRQoL) in moderate-to-severe plaque psoriasis - Mercadal-Orfila, Gabriel; López Sánchez, Piedad; Pou Alonso, Aranzazu; Ibarra-Barrueta, Olatz; Monte-Boquet, Emilio; Borrás Blasco, Joaquin; Padullés Zamora, Nuria; Sanmartin-Fenollera, Patricia; Capilla Montes, Cristina; Bernabéu Martínez, M. Ángeles; Herrera-Pérez, Salvador (Frontiers in Medicine, 2024)
Background and purposePsoriasis is a chronic, immune-mediated inflammatory skin disease that significantly impacts patients’ quality of life. The integration of telepharmacy has the potential to enhance patient care by providing flexible and personalized pharmaceutical follow-up. This study (TELEPROM Psoriasis) evaluates a telepharmacy model for evaluating electronic Patient-Reported outcomes (ePROMs) for individuals with moderate to severe plaque psoriasis in Spain with biological treatment.Experimental approachThis multicenter prospective quasi-experimental study included 258 adult patients initiating or switching biological/immunomodulatory therapy for moderate to severe plaque psoriasis. Patients were recruited from public hospitals in Spain and monitored through the NAVETA telepharmacy platform over a six-month period. PROMs assessed were the Psoriasis Symptoms and Signs Diary and the Dermatology Life Quality Index at baseline, 1 month, 3 months, and 6 months. Data were analyzed using ANOVA, Student’s t-test, multiple regression, and machine learning algorithms to evaluate ePROMs evolution and response and satisfaction with Telepharmacy follow up.Key resultsThe analysis revealed significant influences of gender, employment status, educational level, and daily activity, but no effect of age, on responses to Patient-Reported Outcomes questionnaires. Machine learning models, particularly Random Forest (AUC = 0.98) and Support Vector Machine (AUC = 0.96), effectively predicted patient engagement. DLQI scores significantly decreased from 9.33 ± 7.75 at baseline to 4.34 ± 5.86 at 6 months. Similarly, the PSSD - 7 Days questionnaire showed major reductions, with scores dropping from 55.43 ± 29.94 to 30.73 ± 30.66 at 6 months, and 53% of patients reaching a score of 20 or less. Notably, women reported worse scores at all time points compared to men. Regression analysis explained only 13.2% of the variance in PROMs scores, identifying Employment Status and BMI Range as key contributors.ConclusionThis study demonstrates the efficacy of biologic treatments in significantly improving HRQoL for psoriasis patients. Addressing demographic variables, such as gender, is key for optimizing treatment outcomes and improving ePROMs response rates. Tailored strategies and ML techniques can help identify low-engagement patients and mitigate disparities. Integrating sociodemographic factors into clinical decision-making and patient engagement strategies is fundamental for delivering equitable and comprehensive care.